Analisis Minat Nasabah Dalam Menggunakan Produk Gadai di Bank Syariah Indonesia KCP Sumenep - Holilur Rahman; Intan Permata Sari (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Financing through pawn products is generally available at pawnshop institutions, but along with the development of Islamic finance, Bank Syariah Indonesia (BSI) also participated in financing opportunities for 732 people through pawn. The large interest of these customers needs to be analyzed considering that BSI, a sharia financial institution that initially focused on savings and financing, is currently shifting to pawn products. This study uses a descriptive qualitative research approach with a case study type. Data collection techniques used are observation, interviews and documentation. The results of the study indicate that the marketing strategy of BSI KCP Sumenep offers gold pawn services using Philip Kotler's strategy, namely: product strategy, price, place and promotion and one of the innovations of BSI KCP Sumenep itself is market raids and casual walks (JJS). Advantages The application procedure is very easy to do, the loan process is very fast, the BSI KCP Sumenep gold pawn product itself is able to provide relatively large loan funds, customers receive loans to customer accounts, collateral is stored safely at BSI and notification to customers who pawn gold at BSI when the due date, with that customers are interested in using pawn products at BSI KCP Sumenep.